2020
DOI: 10.1002/mp.14623
|View full text |Cite
|
Sign up to set email alerts
|

Feature‐based automated segmentation of ablation zones by fuzzy c‐mean clustering during low‐dose computed tomography

Abstract: Intra-procedural monitoring and post-procedural follow-up is necessary for a successful ablation treatment. An imaging technique which can assess the ablation geometry accurately is beneficial to monitor and evaluate treatment. In this study, we developed an automated ablation segmentation technique for serial low-dose, noisy ablation computed tomography (CT) or contrast-enhanced CT (CECT). Methods: Low-dose, noisy temporal CT and CECT volumes were acquired during microwave ablation on normal porcine liver (fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…A new method is proposed to measure the similarity level between the value of a categorical attribute of the variable to the center of a categorical cluster . It is based on a method proposed in the article [7]. Binary distance δ(x_ij,a_kj ^t) is used to measure the similarity between the variable and cluster center.…”
Section: The Md-mwfcm Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…A new method is proposed to measure the similarity level between the value of a categorical attribute of the variable to the center of a categorical cluster . It is based on a method proposed in the article [7]. Binary distance δ(x_ij,a_kj ^t) is used to measure the similarity between the variable and cluster center.…”
Section: The Md-mwfcm Algorithmmentioning
confidence: 99%
“…In the traditional clustering technique, a hard-clustering method is used to arbitrarily partition a class of features into one cluster. Although this hard clustering method eliminates ambiguity, it can also cause information loss of that feature as an indicator for another cluster [7]. Therefore, the traditional clustering technique is suboptimal and there is a need for newer techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Bronchiectasis in the right middle lobe and left upper lobe lingual segment is considered an important feature of NTM-LD [ 22 , 23 ]; however, this feature is not rare in patients with MTB-LD [ 24 ]. On the other hand, pleural effusion is rare in the CT images of patients with NTM-LD [ 25 ]. A 2014 study found that 13.3% of patients with NTM-LD had pleural effusion [ 26 ], which may lead to the misdiagnosis of NTM-LD.…”
Section: Introductionmentioning
confidence: 99%
“…Three dimensions-residential network (3D-ResNet) is a classic deep learning framework that is highly recognised for its performance and efficiency. Previous studies have shown that 3D-ResNet achieved surprising results in various medical scenarios, such as recessive ischemic stroke recognition [ 25 ], Alzheimer’s disease classification [ 31 ], thoracic vertebral segmentation [ 32 ], and colonoscopic polyp detection [ 33 ], with an accuracy range of 0.83 from 0.97 in the test set. Additionally, 3D-ResNet has contributed significantly in the diagnosis of lung diseases, such as corona virus disease 2019 (COVID-19) diagnosis using CT scan or chest X-ray (CXR) [ 34 , 35 ], malignancy risk classification of lung nodules using CT scan [ 36 ], non-small cell lung cancer [ 37 ], lung nodules detection [ 38 ], and lung CT image classification [ 39 ], with an accuracy ranging from 0.80 to 0.99 on the test set.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, max-flow min-cuts was used to segment the ablation zone from the background. An automatic approach was taken by Wu et al [ 59 ]. With their method, fuzzy c-mean clustering and cyclic morphology were employed to extract and then refine the ablation zone.…”
Section: Discussionmentioning
confidence: 99%